Cutomer Loyalty in the Age of Digital Sharia Finance: Evidence from Bank Digital Aladin Syariah - Mahsun; Tia Rahmatika; Nurazizah; M. Zainul Ridho; Zilal Afwa Ajidin; Ratna Dewi Kusumawati; Husnul Muamilah (Journal of Finance and Islamic Banking, 2025)
Purpose: This study aims to examine the influence of e-service quality, halal perception, and trust in online platforms on customer loyalty, with customer satisfaction as a mediating variable, focusing on users of Bank Digital Aladin Syariah among Generation Z students. Method: The research employed a quantitative descriptive approach using purposive sampling. Data were collected via structured questionnaires and analyzed using path analysis with multiple linear regression, including F-test and t-test procedures, processed through SPSS version 30. Results: The results indicated that e-service quality, halal perception, and trust in online platforms had a significant direct effect on both customer satisfaction and customer loyalty. However, customer satisfaction did not serve as a mediating variable in the relationship between the three independent variables and loyalty, suggesting that these factors influenced loyalty independently. Implication: The findings provide managerial insights for Islamic digital banking institutions to focus on improving digital service quality, reinforcing Sharia compliance, and building platform trust to foster customer loyalty. Originality: This paper contributes to the literature on Islamic digital finance by integrating technological, ethical, and religious variables into a unified model for explaining customer loyalty. The study offers a novel perspective by focusing on Generation Z users with specific exposure to Islamic banking education and experience.